2004
DOI: 10.1021/ma0359741
|View full text |Cite
|
Sign up to set email alerts
|

HA (Hydrophobic/Amphiphilic) Copolymer Model:  Coil−Globule Transition versus Aggregation

Abstract: For simulating hydrophobic−amphiphilic (HA) copolymers, we have developed a “side-chain” HA model in which hydrophilic (P) interaction sites are attached to hydrophobic (H) main chain, thereby forming amphiphilic (A) monomer units, each with dualistic (hydrophobic/hydrophilic) properties. Using this coarse-grained model, we performed molecular dynamics simulations of the hydrophobically driven self-assembly in a selective solvent, for both single-chain and multichain systems. The focus is on the regime in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 59 publications
6
67
0
Order By: Relevance
“…This conclusion is not affected by the finite concentration effect because it tends to overestimate the dimensions of the polymers in D 2 O and underestimate the dimensions in toluene and methanol. Further collapse of this polymer in D 2 O is expected at higher temperatures, 2 which is consistent with the proposed multistep chain collapse during the coil-to-globule transiton, 27,33 whereas for DP ) 47 and 40, the resulted dimension of the polymers in D 2 O is comparable to or larger than that in toluene and methanol, which is due to finite interactions in the solutions and possible aggregation of a fraction of polymers in D 2 O due to strong end-group attractions. 27 As will be demonstrated below, the end-group interactions facilitate the formation of the polymer dimers in aqueous solutions of short polymer chains with DP ) 8.…”
Section: Polymer Conformation Andsupporting
confidence: 82%
See 3 more Smart Citations
“…This conclusion is not affected by the finite concentration effect because it tends to overestimate the dimensions of the polymers in D 2 O and underestimate the dimensions in toluene and methanol. Further collapse of this polymer in D 2 O is expected at higher temperatures, 2 which is consistent with the proposed multistep chain collapse during the coil-to-globule transiton, 27,33 whereas for DP ) 47 and 40, the resulted dimension of the polymers in D 2 O is comparable to or larger than that in toluene and methanol, which is due to finite interactions in the solutions and possible aggregation of a fraction of polymers in D 2 O due to strong end-group attractions. 27 As will be demonstrated below, the end-group interactions facilitate the formation of the polymer dimers in aqueous solutions of short polymer chains with DP ) 8.…”
Section: Polymer Conformation Andsupporting
confidence: 82%
“…Further collapse of this polymer in D 2 O is expected at higher temperatures, 2 which is consistent with the proposed multistep chain collapse during the coil-to-globule transiton, 27,33 whereas for DP ) 47 and 40, the resulted dimension of the polymers in D 2 O is comparable to or larger than that in toluene and methanol, which is due to finite interactions in the solutions and possible aggregation of a fraction of polymers in D 2 O due to strong end-group attractions. 27 As will be demonstrated below, the end-group interactions facilitate the formation of the polymer dimers in aqueous solutions of short polymer chains with DP ) 8. We note that there are some differences between the polydispersity of the cross-section radius of the polymers in toluene, methanol, and in D 2 O, which can be explained as being due to the relatively sharp interface between the polymer and the solvent in D 2 O 27 as opposed to a rather diffuse interface in toluene and methanol solutions.…”
Section: Polymer Conformation Andsupporting
confidence: 82%
See 2 more Smart Citations
“…The heteropolymer obtained as a result of such a simple one-step procedure can self-assemble into a segregated core-shell microstructure, thus resembling some of the basic properties of globular proteins, particularly their solubility in water. 21,22 Govorun et al 17 has shown that the corresponding chemical sequence is nonalternating and demonstrated the specific long-range correlations (LRCs), which can be described by the statistics of the Lévy-flight type. 23 These correlations are directly related to the CDSD scheme.…”
Section: Cdsd and Long-range Correlated Sequencesmentioning
confidence: 99%